The Influence of Market To Book Value Of Asset Ratio, Market To Book Value Of Equity Ratio, Capital Expenditure To Book Value Of Assets And Earning Per Share On Stock Returns In LQ-45 Companies Listed On The Indonesia Stock Exchange 2013-2018 - Sasmito Bayu Gentur Praptomo; Mariati Tamba; Wardojo (LPPM Universitas Respati Indonesia, 2024)
This study aims to analyze the effect of Market to Book Value of Asset Ratio (MKTBKASS), Market to Book Value of Equity Ratio (MKTBKEQ), Capital Expenditure to Book Value of Asset (CAPBVA), Earning per Share (EPS) on LQ 45 company stock returns on the Indonesia Stock Exchange for the period 2013-2018. This research is an explanatory research that explains the causality relationship using secondary data with a population of 45 companies incorporated in the LQ45 index on the Indonesia Stock Exchange in 2018. A sample of 35 companies were selected using the purposive sample method in accordance with predetermined criteria, one of which was to have a report finance in 2013-2018. The analytical method used is panel data regression. The results of this study indicate that partially, with a 95% confidence level Market to Book Value of Equity Ratio (MKTBKEQ) and Earning Per Share (EPS) significantly influence the LQ 45 company stock returns. Meanwhile Market to Book Value of Asset Rati (MKTBKASS) and Capital Expenditure to Book Value of Asset (CAPBVA) partially do not significantly influence the LQ45 company's stock returns. Simultaneously, all variables together affect the value of stock returns. Meanwhile based on the coefficient of determination obtained, it can be concluded that all independent variables are able to explain 21.64 percent of the variation in the stock prices of LQ 45 companies in Indonesia during 2013-2018 while the rest are explained by other variables. Keywords : Market to Book Value of Asset Ratio (MKTBKASS), Market to Book Value of Equity Ratio (MKTBKEQ, Capital Expenditure to Book Value of Asset (CAPBVA), Earning Per Share (EPS) and Stock Return